What Does American History Tell Us about Katrina and Vice Versa? - Powell, Lawrence N. (Journal of American History, 2007)
The article discusses political aspects of damage caused by Hurricane Katrina in New Orleans, Louisiana. The author discusses promises by politicians to rebuild cities following disasters and how emergencies can lead to the curtailing of civil rights and changes in government. He suggests that reconstruction efforts in New Orleans provided economic opportunities to companies with political connections. New Orleans mayor C. Ray Nagin rejected a plan by the development group Urban Land Institute (ULI) to focus reconstruction away from flooded areas. The state recovery program the Road Home failed to provide most residents with grants. The author suggests Hurricane Katrina has focused attention on infrastructure needs and insurance regulation.